COVID-19 as external enabler of entrepreneurship practice and research - Per Davidsson; Jan Recker; Frederik von Briel (BRQ Business Research Quarterly, 2021)
For decades, entrepreneurship and strategy research has been dominated by agent-centric and inward-looking theoretical perspectives. The ongoing COVID-19 pandemic demonstrates the limits of this stance, as its influence on business has been both enormous and palpable. For the most part, the effects of the pandemic are no doubt negative. Business research - and presumably business practice - typically address such influence in terms of failure, resilience, and crisis management among existing businesses. Contrasting this prevalent discourse, we focus instead on positive influence of the pandemic for some emerging and new ventures. We analyze the many possible positive effects on entrepreneurship practice and highlight also positive effects on entrepreneurship research. We illustrate both positives by applying the External Enabler framework.
Keywords: L26; M13; O3; R11; 650; COVID-19; crisis; entrepreneurship; External Enabler; venture creation